The Legality of Tiktok in Indonesia - Izzatur Rahman, Rafika; Betsy Prajna Paramita; Muhammad Tri Mulya Putra; Sellyana Narita Ratih Wulandari (Jurusan Ilmu Hukum Fakultas Syariah dan Hukum uin alauddin, 2024)
The 21st century marks a significant communication and information exchange shift, making it progressively more effortless, cost-effective, and efficient. Consequently, conventional communication and information media are gradually marginalized, often perceived as less effective and efficient. TikTok, a short-form video platform designed to foster user creativity through content creation and sharing, was launched in September 2016. It gained a global presence before expanding into Indonesia in 2018. However, concerns regarding the spread of negative content led to a temporary block by the Indonesian Ministry of Communication and Information Technology. The block was lifted on the condition that TikTok adheres to existing Indonesian regulations. This research employs a legal research methodology, utilizing both a statutory and a conceptual approach. The operation of TikTok in Indonesia with a user base exceeding 112.9 million, without adopting the Limited Liability Company (LLC) structure, warrants further investigation as it undoubtedly impacts its economic activities in the country. In this instance, TikTok, operating as an Electronic System Operator and offering paid services to users through its electronic system, must be recognized as a business entity. In Indonesia, the Ministry of Communication and Information legally obligates all digital platforms and social media to register as Electronic System Operators (ESOs). The regulations concerning Electronic System Operators (ESOs) are outlined in Law Number 19 of 2016 regarding Electronic Information and Transactions, Government Regulation Number 71 of 2019 regarding the Implementation of Electronic Systems and Transactions, and Regulation of the Minister of Communication and Informatics Number 5 of 2020 concerning Private Electronic System Operators.